Circulating mir‐320a promotes immunosuppressive macrophages M2 phenotype associated with lung cancer risk. Issue 11 (6th January 2019) - Fortunato, Orazio; Borzi, Cristina; Milione, Massimo; Centonze, Giovanni; Conte, Davide; Boeri, Mattia; Verri, Carla; Moro, Massimo; Facchinetti, Federica; Andriani, Francesca; Roz, Luca; Caleca, Laura; et al.
Abstract : miRNAs play a central role in the complex signaling network of cancer cells with the tumor microenvironment. Little is known on the origin of circulating miRNAs and their relationship with the tumor microenvironment in lung cancer. Here, we focused on the cellular source and relative contribution of different cell types to circulating miRNAs composing our risk classifier of lung cancer using in vitro/in vivo models and clinical samples. A cell‐type specific expression pattern and topography of several miRNAs such as mir‐145 in fibroblasts, mir‐126 in endothelial cells, mir‐133a in skeletal muscle cells was observed in normal and lung cancer tissues. Granulocytes and platelets are the major contributors of miRNAs release in blood. miRNAs modulation observed in plasma of lung cancer subjects was consistent with de‐regulation of the same miRNAs observed during immunosuppressive conversion of immune cells. In particular, activated neutrophils showed a miRNA profile mirroring that observed in plasma of lung cancer subjects. Interestingly mir‐320a secreted by neutrophils of high‐risk heavy‐smokers promoted an M2‐like protumorigenic phenotype through downregulation of STAT4 when shuttled into macrophages. These findings suggest a multifactorial and nonepithelial cell‐autonomous origin of circulating miRNAs associated with risk of lung cancer and that circulating miRNAs may act in paracrine signaling with causative role in lung carcinogenesis and immunosuppression. Abstract : What's new? microRNAs play a central role in the complex signaling network of cancer cells with the tumor microenvironment. However, little is known on the origin of circulating miRNAs and their mechanisms of action. This study found a multifactorial and non‐epithelial cell‐autonomous origin of circulating miRNAs associated with lung cancer risk. The findings also suggest a link between an immunosuppressive and pro‐tumorigenic microenvironment and modulation of circulating miRNAs associated with lung cancer risk. The authors propose a novel mechanism whereby miRNA released by neutrophils induce macrophage polarization to support lung cancer growth, highlighting the potential for reprogramming macrophages toward an anti‐tumor polarization.